Report: Proposed New Interior Design of Malaysian Red Devils Cafe and Fan Club for Mr.Laurance How at No. G13A & 113A Blok 2, Laman Seri Business Park, Persiaran Sukan Seksyen 13,40000 Shah Alam, Selangor Darul Ehsan / Muhamad Azrul Aziz - Aziz, Muhamad Azrul (Faculty of Architecture, Planning and Surveying, 2012)
The final project for the student of Diploma in Interior Architecture is a manisfestation towards the student’s knowledge about the world aspect on interior design that had been learn from basic to the final presentation on the proposed design. The project have been chosen for the final project is proposed new interior design of Malaysian Red Devils Cafe and Fan Club at no. G13A & 113A, Block 2, Laman Seri Business Park, Persiaran Sukan, Seksyen 13 , 40000 Shah Alam , Selangor Darul Ehsan This proposed Malaysian Red Devils Cafe and Fan Club is to attract costumer, mostly the Mancheter United fans to come and gather at the fan club cafe always.The target customer is all the Manchester United fans. Concept and image that had been chosen not only must be suitable with the clients as both of it would reflect the client itself, but at the same time it would give a positive impact to the Before start to do work of designing, the students also need to do research work on existing space, such as issues and problems that coincided with objectives of the study.